Loss Analysis of Propulsion System on an Electric Railway - Jamal, Agus; Chamim, Anna Nur Nazilah; Putra, Karisma Trinanda; Lestari, Sri Indah; Jusman, Yessi (Journal of Electrical Technology UMY, 2018)
Electric Railway (KRL) is a train that is based on eletrification system. The electrification system in the KRL supplies electrical energy to the train locomotive and several other carriage units, so the train can run. Electrical energy can be either AC or DC source. There are two electrical systems to support the performance of KRL, propulsion system and auxiliary system. The propulsion system is a driving system and than the auxiliary system is the system that handles the electrical load on KRL. In this research, discuss about the loss of propulsion system on KRL LAA Electric DC, AC Traction Motor. The propulsion system consists of several components, such as pantograph, circuit breaker, capacitor filter, IGBT VVVF inverters and AC traction motors. The component has different losses and different efficiencies. There are five test conditions for AC traction voltage inputs of 160.5V, 321V, 493.9V, 635V and 645V. By calculating using equations, from the five test conditions it can be seen that the propulsion system has the lowest power loss with the highest efficiency at the input voltage of AC 635V traction motors, which obtained the power loss of inverter VVVF IGBT 41.996kW with the efficiency 90.67% and the power loss of AC traction motor 18.219kW with the efficiency 91.45%.